Chemical Exchange Saturation Transfer (CEST): what is in a name and what isn’t? - van Zijl, Peter C.M. (2011)
Chemical exchange saturation transfer (CEST) imaging is a relatively new MRI contrast approach in which exogenous or endogenous compounds containing either exchangeable protons or exchangeable molecules are selectively saturated and, after transfer of this saturation, detected indirectly through the water signal with enhanced sensitivity. The focus of this review is on basic MR principles underlying CEST and similarities to and differences with conventional magnetization transfer contrast (MTC). In CEST MRI, transfer of magnetization is studied in mobile compounds instead of semisolids. Similar to MTC, CEST has contributions of both chemical exchange and dipolar cross-relaxation, but the latter can often be neglected if exchange is fast. Contrary to MTC, CEST imaging requires sufficiently slow exchange on the MR time scale to allow selective irradiation of the protons of interest. As a consequence, magnetic labeling is not limited to radio-frequency saturation but can be expanded with slower frequency-selective approaches such as inversion, gradient dephasing and frequency labeling. The basic theory, design criteria, and experimental issues for exchange transfer imaging are discussed. A new classification for CEST agents based on exchange type is proposed. The potential of this young field is discussed, especially with respect to in vivo application and translation to humans.